Effect of Recycled Tire Rubber and Marble Waste on Fresh and Hardened Properties of Concrete - Djebien, Rachid; Bouabaz, Amel; Abbas, Yassine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper investigates the effect of simultaneous adding of recycled tire rubber (RTR) and marble waste (MW) as fine aggregates on the properties of concrete. To achieve this objective, the particles size distribution of crushed sand (CS) was corrected by the use of marble waste sand (MWS), and RTR was used by volumetric substitution (1%, 2%, 3% and 4%) of aggregates in concrete. The fresh properties were investigated using the slump, density and air content tests.
Keywords: recycling tire rubber; marble waste; green concrete; properties; odpady gumowe; odpady marmurowe; recykling; beton